Islam, Tradition, and Modernity: A Living Hadits Analysis of the Transformation of Sound Symbols for Iftar Time in Banjar Society - Uria Hasnan; Jalaluddin Jalaluddin; Zainal Abidin; Zaki Mubarak (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to analyze the transformation of sound symbols used to mark iftar time in Banjar society through the perspective of living hadith, with particular attention to the interaction between Islam, local tradition, and modernity. The research investigates how prophetic teachings concerning the determination of iftar time have been interpreted, embodied, and transformed through different auditory symbols, ranging from direct observation of sunset, the adhan, and the beduk to contemporary digital notifications. This study employs a qualitative library research method utilizing classical hadith collections, works of Islamic scholarship, living hadith studies, sociological analyses of religion, and contemporary literature on digital religiosity. The findings reveal that the transformation of sound symbols does not alter the normative foundation of the prophetic tradition but reflects a dynamic process of adaptation to changing socio-cultural and technological contexts. In Banjar society, the beduk functions not only as an auditory marker of iftar but also as a symbol of collective memory, cultural identity, and religious education. The transition toward digital notifications demonstrates the continuing relevance of prophetic teachings in contemporary Muslim life. The novelty of this study lies in its integration of living hadith theory, sound symbolism, Banjar Islamic culture, and modern digital religiosity to explain how religious traditions maintain continuity while simultaneously accommodating cultural and technological transformations